Narrativised teacher cognition of classroom interaction: articulating foreign language practice in the Amazonian context - Silva, Maristela (2016)
This thesis investigates teacher cognition of classroom interaction as represented in narratives by Amazonian language teachers. Language teacher cognition has been investigated in the great educational centres in Brazil, but has been overlooked as a research theme in Amazonas, the context of this study. In order to bridge this existing gap in language teacher research, the current study develops a narrative enquiry in the public and private school settings to find the different understandings of interaction in the English as a foreign language (heretofore EFL) classroom as articulated by teachers. The study is grounded in theories of teacher education and cognition, applied and socio-linguistics, socio-cultural theories and discourse analysis to further the understanding of concepts that are of rising importance in the EFL field: teacher cognition, classroom interaction, and narrative research. In brief, teacher cognition refers to teachers’ mental lives and to the ways they perceive their practice. In this research, four constructs (knowledge, thought, beliefs, and decision-making) are considered to represent the broad conceptualisation of teacher cognition. Classroom interaction corresponds to the collaborative moments which happen in the language classroom among students, or between students and teacher, in order to improve learning. Narrative enquiry relates to both the method and methodology which is used to understand diverse knowledge processes. In simple terms, in this thesis, narrative enquiry explores teachers’ stories about their practice and determines the ways in which they can be analysed and interpreted. This qualitative research has been designed from a constructionist epistemological standpoint and an interpretivist theoretical perspective. Because it investigates complex concepts, this research does not follow one specific philosophical background but finds inspiration in critical pedagogy and matters of knowledge in the Brazilian context. The data produced by nine experienced EFL teachers was systematically analysed. Starting from the four individual constructs of teacher cognition, the interpretation of the data develops to concepts and themes which emerged from this initial analysis. The findings generated new understandings of the construction of knowledge as personal practical knowledge (PPK) and its relationship to other constructs of teacher cognition, to experience, to the teachers’ individual contexts and to styles of storytelling. From these main findings, the present study proposes a model of narrativised teacher cognition to better understand the interrelation between the cognitive constructs and discursive strategies, as well as build a new and concrete dimension to teachers’ articulation of their practice.